Increasing Tourist Attraction at Sumber Dhuwur, Wonosari Village, Ngoro District, Mojokerto Regency: Meningkatkan Daya Tarik Wisatawan di Sumber Dhuwur Desa Wonosari Kecamatan Ngoro Kabupaten Mojokerto (Indonesian Journal of Cultural and Community Development, 2024)
Community service activities are one of the mandatory activities at Muhammadiyah University of Sidoarjo, where this service activity takes the form of the Enlightenment Real Work Lecture program. One of the work program areas that is the main focus is the tourism sector. The aim of this work program is to increase the number of tourist visits to Sumber Tourism. Service activities carried out at the Sumber Dhuwur tourist attraction, Wonosari Ngoro, Mojokerto. The method used in collecting data was observation, interviews and documentation which were analyzed using qualitative descriptive analysis. This service activity can provide exposure and increase awareness of Sumber Dhuwur tourism through Instagram social media.